PENGGUNAAN MEDIA PEMBELAJARAN IPS TENTANG KEBERAGAMAN BUDAYA DI SD - Rona Fristi Febbilla; Riska Ayuning Tiyas, Uswatus Ni’mah, Shabrina Khilda Zulfia, Ika Oktavianti (CV. ADIBA ASIHA AMIRA, 2025)
Social studies learning about cultural diversity aims to form students' understanding of the importance of tolerance, mutual respect, and maintaining diversity in everyday life. However, in the learning process, students often have difficulty. One solution that can be implemented is the use of learning media in teaching the topic of cultural diversity in social studies classes. The aim of this research is to analyze learning media that can improve the quality of students' understanding of the importance of maintaining cultural diversity in Indonesia and also to find out the types of teaching media in social studies learning on cultural material. This research method uses a literature study approach. The results of this research are that social studies learning about culture can be carried out using the help of teaching media. Using teaching media can help students understand cultural concepts. Learning media has three functions, namely 1.) effective function, 2.) cognitive function, and 3.) compensatory function.